Inventarisasi dan Identifikasi Tungau pada Mawar di Kabupaten Ogan Ilir, Provinsi Sumatera Selatan - Indayani Indayani; Ahmad Sultoni Pulungan; Darma Prasatya; Miranda Miranda; Nisa U Mardiyah; Safira Cahaya Ramadhani; Abu Umayah; Bambang Gunawan; Arsi Arsi (Pusat Unggulan Riset Pengembangan Lahan Suboptimal (PUR-PLSO) Universitas Sriwijaya, 2023)
Indayani I, Pulungan AS, Prasatya D, Miranda M, Mardiyah NU, Ramadhani CS, Umayah A, Gunawan B, Arsi A. 2022. Inventory and identification of mites on roses in Ogan Ilir District, South Sumatra Province. In: Herlinda S et al. (Eds.), Prosiding Seminar Nasional Lahan Suboptimal ke-10 Tahun 2022, Palembang 27 Oktober 2022. pp. 751-758. Palembang: Penerbit & Percetakan Universitas Sriwijaya (UNSRI).Roses are widely cultivated by the public because of their beautiful and beautiful appearance as well as their fragrant and distinctive aroma, so they are nicknamed the queen of flowers, but on the other hand, roses are easily attacked by various species of mites. This study aimed to determine the species of mites on roses so that this research can make it easier to recognize and overcome the symptoms of mite attacks on roses. This research was conducted in the villages of Timbangan, Palem Raya, Sembabu Island, and Tanjung Sejaro, North Indralaya District, Ogan Ilir Regency, South Sumatra Province using survey and sampling methods. The results of the study have obtained 2 species of mites with the genus Tetranychus spp. The spread of mites occurs rapidly due to wind and human activities. Mites are polyphagous, so the possibility of expanding the host due to this pest should be watched out for. Mites attack can cause the process of formation of leaves and stems to be hampered so that the productivity of ornamental plants decreases. The mites damage the plant by sucking the liquid from the leaf cells which results in pale spots due to the damaged epidermal cells due to being sucked in. Although the individual damage caused by mites is small, with a population of thousands of mites attacking plants, it will cause more injuries so that it can reduce the photosynthetic ability of plants. So, roses are plants that are liked by many people but are often attacked by mites. It is better if the rose has been attacked by mites to minimize the spread of the attack, it is expected to spray pesticide liquid, rely on natural enemies, and plant high-yielding varieties.